(untitled) (Colombia Medica, 2014)
Polythelia has been defined as the presence of supernumerary nipples without accessory glandular tissue. Usually, these growths follow imaginary mammary lines running from the armpits to the groin. Although the presence of dental anomalies may occasion only a simple cosmetic problem with specific clinical considerations, the association with family polythelia has been scarcely reported. This paper reports on a case of polythelia that is associated with dental anomalies in an Argentine family and discusses suggestions for a thorough dental history and medical consultation to prevent possible pathological conditions or potential malignant transformation of mammary tissues.